PENGENDALIAN PEREDARAN GELAP NARKOTIKA OLEH NARAPIDANA DARI DALAM LEMBAGA PEMASYARAKATAN (LAPAS) - Artha, I Gede; Wiryawan, I Wayan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p14, 2015)
Drug smuggling by high and sophisticated operation mode recently was able reach the prisoner which is as society prison status. Law enforcement officer especially the police in conducted their function as law enforcement to the prisoner that involved in drug smuggling, in disclosure and sttlement their case (investigation step) did not easy because the prisoner was a society in prison encironment. There are two problem in this research : 1. why the conected and correlated of the legal system for drug ? 2. Why the drug smuggling is high operation by the prisoner which is as society prison status and to up from in the prison ? The result of this research show that the law enforcement to the doer drug smuggling by the law enforcer. Should faced ethic code profesion society, there for it was impossible for the law the optimize of law enforcement by law enforcer to the doer of drug smuggling in prisoner society such as intern and extern efforts, where the intern effort include increase the coordination function and cooperation between the law enforcement especially with the prison officers.
Keywords: Doer of Drug Smuggling, by Prisoner from in the Prison